Enantioselective cooperative catalysis - Inamdar, Suleman M.; Shinde, Valmik S.; Patil, Nitin T. (Organic & Biomolecular Chemistry, 2015)
In recent years, enantioselective cooperative catalytic reactions, wherein two catalysts work simultaneously to form products which cannot be obtained by the use of a single catalyst alone, have attracted considerable attention. This review focuses on this emerging field, with particular emphasis on mechanistic aspects, which will help readers to understand the role of each catalyst.